Analysis Risk Factors of Asphyxia Neonatorum - Agustin Dwi Syalfina; Shrimarti Rukmini Devy (Universitas Airlangga, 2015)
Antenatal care is designed to promote, protect, and maintain the health during pregnancy and reduce maternal and neonatal mortality. The scope of antenatal care also includes the detection and special care for high risk cases as well as the prediction and prevention of complications during pregnancy and childbirth. Complications of pregnancy and childbirth causes of neonatorum asphyxia. Neonatorum asphyxia is a condition where the baby can not breathe spontaneously and regularly after birth. Neonatorum asphyxia cases in Mojokerto district has 46.9% in 2010 and 39.7% in 2014. This aim of this study was to analyze the effect of the quality of antenatal care to neonatorum asphyxia in Mojokerto. The type of this study was observational analytic with case control design with a sample of cases and controls amounted to 80 babies. Data was analyzed using univariate, bivariate and multivariate analysis with logistic regression. The results of this study showed that the quality of antenatal care was significant with neonatorum asphyxia (OR = 8,556; 95% CI:2,777-26,358). Confounding variables associated with neonatorum asphyxia were maternal occupation (OR = 4,558;95% CI:1,391- 14,298), primary education (OR = 21,620; 95% CI: 1,932-241,886), secondary education (OR = 20,977; 95%CI: 1,819-241,872). The conclusion quality of antenatal care has effect of nenatorum asphyxia. Suggestions can be drawn based on the results of this study are for health workers are expected to do health education to the public and families about the importance of antenatal care and antenatal care services that should be obtained from health workers. Keywords: quality of antenatal care, neonatorum asphyxia, case control